Interacción entre Salvinia minima y Lemna gibba: efecto sobre el crecimiento en distintos medios de cultivo - de Cabo, Laura Isabel (2009)
Nutrient uptake and competitive ability of the aquatic species Lemna gibba and Salvinia minima were evaluated. The experiment was carried out in a greenhouse and plants were grown as mono-plant cultures and mixed-plant cultures. Three different me-dia were used: tap water and the chemically defined media Lemna and Hutner 1/10. Du-ration of the experiment was 7 days. Initial and final dry weights and DIN and SRP con-centrations were determined. Relative growth rates (RGR) and nutrient uptake rates were calculated. L. gibba´s RGR values increased significantly in Hutner 1/10 medium when types of cultures were analyzed separately. RGR values decreased in Lemna and Hutner 1/10 media in mixed-plant cultures. S. minima did not show significant differences in its RGR values. In mono-plant cultures N and P uptake rates in Lemna medium were sig-nificantly larger for L. gibba. In Hutner 1/10 medium P uptake rate was greater for S. min-ima and N uptake rate was larger for L. gibba. The presence of S. minima negatively affected L. gibba´s growth.